Design And Implementation Of The Latulip Integrated Service Pos Information System Using The Gulud Regression Method - Ria Irawati; Rohmat Nur Ibrahim; Adi Suwarno; Berry Lesmana; Dewi Fawziawati (Informatics Management, Engineering and Information System Journal, 2025)
The Latulip Integrated Service Post is essential for overseeing maternity and child health within the community.  An integrated information system has been designed utilising the rolling regression method to improve the efficiency and efficacy of data management and facilitate superior decision-making.  This system is designed to oversee critical components of the integrated service post, encompassing child data, maternal data, immunization schedules, child development monitoring, activity schedules, and health articles.  The system offers easily accessible and interactive capabilities through three primary stakeholders: parents, community health workers, and administrators.  The rolling regression technique is utilised to examine and forecast child development using existing historical data.  This analysis enables the system to provide more precise recommendations regarding children's health needs and to monitor their development consistently.  The deployment of this method has demonstrated efficacy in enhancing the quality of information provided to users and aiding community health professionals in making more informed decisions about health interventions.  The findings demonstrate that the Latulip Integrated Service Post information system can proficiently integrate diverse data, deliver reliable analysis, and provide substantial support for the operations of the integrated service post.  Consequently, this system is anticipated to function as a prototype for the creation of more integrated service information systems across diverse geographies.